Karakteristik Transformator terhadap Arus Harmonik - Sukmadi, Tejo (Departemen Teknik Elektro, Universitas Diponegoro, 2011)
Electric power have become one of the primary need of modern society. Most of electrical equipments in this time represents as non linear loads. In the electric power system, a non linear load represents as harmonic source. The generated harmonic load currents will flow back into electric power source passing through the transformers. These harmonic currents will become smaller in their amplitude when passing the transformer even some higher order harmonics components will be suppresed. This research is conducted as a mean to know how far transformers could reduced harmonic currents amplitude and to investigate what higher order harmonic current compenents would be suppresed after passing the transformers. Keywords : Transformator, harmonic current, amplitude.